2019
DOI: 10.1101/542613
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Descriptive epidemiology of energy expenditure in the UK: Findings from the National Diet and Nutrition Survey 2008 – 2015

Abstract: Background Little is known about population levels of energy expenditure as national surveillance systems typically employ only crude measures. The National Diet and Nutrition Survey (NDNS) in the UK measures energy expenditure in a 10% subsample by goldstandard doubly-labelled water (DLW).Methods DLW-subsample participants from the NDNS (383 males, 387 females) aged 4-91yrs were recruited between 2008 and 2015. Height and weight were measured, and bodyfat percentage was estimated by deuterium dilution. Result… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 32 publications
7
2
0
Order By: Relevance
“…Our results indicate that men accumulate higher levels of PAEE than women across all ages; a finding consistent with other descriptive studies [7,[22][23][24]. Men also accumulate higher levels of MVPA and expend more of their energy at higher intensities than women.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results indicate that men accumulate higher levels of PAEE than women across all ages; a finding consistent with other descriptive studies [7,[22][23][24]. Men also accumulate higher levels of MVPA and expend more of their energy at higher intensities than women.…”
Section: Discussionsupporting
confidence: 92%
“…Among both men and women PA was lower in older individuals. Moreover, the levels and age-associated differences in PAEE demonstrated in Figure 1 are similar to that recently reported in UK nationally representative samples [7], and the age association remained significant in multivariable analysis (Table 2). Although PAEE and MVPA were highest in young adults, the pattern of association with age was quite different.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Movement and PAEE were both lower in the older age groups, a similar result to that observed in other population studies (2,32,33). We observed that older participants (60-65 age group) spend a large proportion of their time in postures that are similar to those with high BMIs, particularly in men.…”
Section: Discussionsupporting
confidence: 90%